Fragment-Hopping-Based Discovery of a Novel Chemical Series of Proto-Oncogene PIM-1 Kinase Inhibitors - Saluste, Gustavo; Albarran, Maria I.; Alvarez, Rosa M.; Rabal, Obdulia; Ortega, Miguel Angel; Blanco, Carmen; Kurz, Guido; Salgado, Antonio; Pevarello, Paolo; Bischoff, James R.; Pastor, Joaquin; Oyarzabal, Julen (PLOS ONE, 2012)
A new chemical series, triazolo[4,5-b]pyridines, has been identified as an inhibitor of PIM-1 by a chemotype hopping strategy based on a chemically feasible fragment database. In this case, structure-based virtual screening and in silico chemogenomics provide added value to the previously reported strategy of prioritizing among proposed novel scaffolds. Pairwise comparison between compound 3, recently discontinued from Phase I clinical trials, and molecule 8, bearing the selected novel scaffold, shows that the primary activities are similar (IC50 in the 20 to 150 nM range). At the same time, some ADME properties (for example, an increase of more than 45% in metabolic stability in human liver microsomes) and the off-target selectivity (for example, an increase of more than 2 log units in IC50 vs. FLT3) are improved, and the intellectual property (IP) position is enhanced. The discovery of a reliable starting point that fulfills critical criteria for a plausible medicinal chemistry project is demonstrated in this prospective study.